KINERJA KEUANGAN DITINJAU DARI PERIMBANGAN KEMANDIRIAN, PERIMBANGAN EFEKTIVITAS, PERIMBANGAN EFISIENSI DAN PERIMBANGAN PERTUMBUHAN SAAT PANDEMI COVID-19 - Nur Ida Iriani; Totok Sasongko; Yuliana Indah Sari (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
The purpose of this study was to determine the financial condition of the village before and after the Covid-19 pandemic, the results of the village's financial work after being calculated using specific financial ratios for public sector organizations. The method was descriptive quantitative. The technique used was observation of the object under study and conducting interviews. The results of this study indicate that the financial condition of Landungsari Village has increased in 2019 and 2020 through the Village Original Income that has been obtained. The independency ratio of Landungsari Village has decreased in 2020 by 83.65% with a consultative relationship pattern. The effectiveness ratio remains the same in 2019 and 2020, which is 100% and is categorized as effective. The efficiency ratio has decreased in 2020 by 221.64% which is categorized as sufficient efficiency. The growth ratio showed that financial performance was going well and achieving positive growth. The financial condition of Landungsari Village was not significantly affected by the Covid-19 pandemic seen from the increase in Village Original Opinion in 2019 and 2020. The financial performance of Landungsari Village in 2019 and 2020 has been said to be good, seen from the performance of independence, effectiveness and growth running well despite efficiency performance still low